Understanding, Acceptance, and Habituation of Pancasila Behavior from the Implementation of the Pancasila P5 Student Profile Strengthening Project on Global Cooperation and Diversity at SMA Negeri 4 Singaraja - Yulia, Komang Yulia Purnama Yanti; Sukadi, Sukadi; Budiarta, I Wayan (Program Studi PPKn Jurusan Hukum dan Kewarganegaraan Undiksha Singaraja, 2025)
Abstract This study examines the implementation of the Pancasila Student Profile Strengthening Project (P5) with a focus on global diversity at SMA Negeri 4 Singaraja, Bali, using a descriptive qualitative approach with a case study design. Data was collected through interviews, observations, document analysis, and focus group discussions to explore the planning process, teacher and student perceptions, and instilled values about global diversity. The findings show that the POACR (Planning, Organizing, Mobilizing, Controlling, Reflecting) strategy supports activities such as cultural video analysis, watching collective films on diversity, and interviews with resource persons, improving students' understanding of